Frontiers in zoology (BioMed Central, 2004)
Frontiers in Zoology is the first Open Access journal focusing on zoology as a whole. It aims to represent and re-unite the various disciplines that look at animal life from different perspectives and at providing the basis for a comprehensive understanding of zoological phenomena on all levels of analysis.